Wing variation in tribe limenitidini (Nymphalidae: Limenitidinae) from Sarawak, Malaysia - Wan Nurainie Wan Ismail,; Sofea Noor Mustafa,; Ratnawati Hazali,; Nurul Zawiyah Mohamad,; Hazirah Mohd Tamin Nor, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study describes and compares the wing pattern variation among species of the tribe Limenitidini. A total of 34 species representing 13 genera of the tribe Limenitidini wing were examined and illustrated, where pattern elements of the nymphalid ground plan (NGP) are labelled in color. In general, the ventral wing surface tends to have more visible pattern elements than the dorsal wing surface. Elements c (basal symmetry system), d (proximal band of central symmetry system), f (discal band of central symmetry system) and I (parafocal element) are the common pattern elements found among species examined of this tribe. UPGMA were constructed to show the similarity distance between the species of tribe Limenitidini in terms of pattern elements on the ventral wing surface. The sexual dimorphism and colour resemblance among species in this study are also discussed.